DECOMPOSITION RATE OF THREE TYPES OF LEAF LITTER, ARTHROPODS DIVERSITY, AND SOIL CHEMISTRY AT COFFEE AGROFORESTRY - Syafia Shani, Nadiya
Healthy and fertile soil conditions can meet the nutritional needs of plants that grow on it. Decomposition is one of the significant processes in the circulation of nutrients in the ecosystem. The decomposition process involves physical, chemical, and biological agents such as Arthropods. Arthropods are important decomposers in tropical ecosystems as agents of fragmentation. This study aims to analyze the rate of decomposition of three types of litter in coffee agroforestry and the diversity of Arthropods in them. This research was conducted in Palintang coffee agroforestry, North Bandung, West Java. Coffee, eucalyptus, and goatweed are the dominant vegetation in the research area. Ten plots each under the coffee tree were determined and each plot was placed with 18 litter bags measuring 20x23 cm with 1 mm mesh size, each containing 10 g of coffee, eucalyptus, and goatweed dry litter for a total of 180 litter bags. Every 4-weeks, 30 litter bags were taken, weighed, and extracted using the Barlese-Tullgren method to obtain Arthropods, then separated, counted, and identified. Under litterbag soils were tested for their chemical content. The study was conducted for 6-months starting from November 2020 to April 2021. The results showed that the litter biomass had decreased: goatweed litter by 88.65%, coffee by 50.23%, and 79% in 6 months. The highest individual richness was found in December for coffee, eucalyptus, and goatweed which are 8781, 6218, and 4897. In coffee and eucalyptus litter, the highest species richness was found in February, while in goatweed litter in December which are 64, 63, and 48 species. Litter mass loss was more affected by individual richness than species. The most commonly found Arthropods are the Collembolan group. During the 6-months study, the fastest decomposition rate occurred in goatweed litter, and the most affected soil chemical elements were Boron and exchangeable K.